Perceived effects of COVID-19 restrictions on smallholder farmers: Evidence from seven lower- and middle-income countries - Hammond, James; Siegal, Kim; Milner, D.; Elimu, E.; Vail, T.; Cathala, P.; Gatera, A.; Karim, A.; Lee, Ja-Eun; Douxchamps, Sabine; Thanh Tu, Mai; Ouma, Emily A.; et al. (Elsevier, 2022)
CONTEXT